2012
DOI: 10.1007/s12011-012-9484-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zinc Ions on Differentiation of Bone Marrow-Derived Mesenchymal Stem Cells to Male Germ Cells and Some Germ Cell-Specific Gene Expression in Rams

Abstract: This is the first report to describe the effects of zinc (Zn) ions on the expression of germ cell (GC) genes from bone marrow-derived mesenchymal stem cells (BM-MSCs). Zn plays an important role in germinal epithelium maintenance, testosterone secretion, differentiation of GCs, and spermatogenesis. In addition, several studies have suggested that MSCs have the potential for differentiation into numerous cells types, including male GCs. In this study, we have treated passage-3 ram BM-MSCs with 0.14 μg/ml Zn sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…After 15–20 min, alizarin red 40 mM (pH 4.1) was added to each well. The plates were incubated at room temperature for 20 min with shaken and then they were washed 2–3 times with PBS shaken for 5 min to reduce nonspecific staining [5, 36]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After 15–20 min, alizarin red 40 mM (pH 4.1) was added to each well. The plates were incubated at room temperature for 20 min with shaken and then they were washed 2–3 times with PBS shaken for 5 min to reduce nonspecific staining [5, 36]. …”
Section: Methodsmentioning
confidence: 99%
“…Chondrogenic differentiation medium composed of high-glucose DMEM with 10% FBS, 100 U/mL penicillin, 100 μg/mL streptomycin, 1.3 mM L-ascorbic 2-phosphate, 0.01 mM dexamethasone and ITS+1 Liquid Media Supplement (100x) was used for 14 days. At the end of chondrogenesis, cells were fixed with 4% (v/v) paraformaldehyde for 30 min, washed with PBS for three times and proteoglycans were stained with 0.1% toluidine blue [36]. …”
Section: Methodsmentioning
confidence: 99%
“…The RT-PCR process was performed according to former reports (33, 34). Briefly, TRIzol reagent (Invitrogen, Paisley, UK) was used to extract total RNA from the cells according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…1). Some evidence has shown that germ-like cells can be generated from somatic stem cells derived from mouse [30,31], sheep [32,33], or human [34][35][36] mesenchymal stem cells; fetal mouse skin [37,38] as well as porcine skin [39][40][41][42] or muscle [42,43] stem cells; and human amniotic fluid stem cells [44,45]. Combined, these studies provide examples in which somatic stem cells differentiated into male or female germ cells in culture.…”
Section: Germ Cell Differentiation From Somatic Stem Cellsmentioning
confidence: 99%